2018
DOI: 10.1073/pnas.1806573115
|View full text |Cite
|
Sign up to set email alerts
|

Stunted childhood growth is associated with decompartmentalization of the gastrointestinal tract and overgrowth of oropharyngeal taxa

Abstract: Linear growth delay (stunting) affects roughly 155 million children under the age of 5 years worldwide. Treatment has been limited by a lack of understanding of the underlying pathophysiological mechanisms. Stunting is most likely associated with changes in the microbial community of the small intestine, a compartment vital for digestion and nutrient absorption. Efforts to better understand the pathophysiology have been hampered by difficulty of access to small intestinal fluids. Here, we describe the microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
183
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(213 citation statements)
references
References 98 publications
(89 reference statements)
13
183
5
3
Order By: Relevance
“…However, although it is not frequently addressed, it appears that gastric and duodenal microbiota share many common features . Microbiota analysis of African children showed that the stomach and duodenum microbiota are alike but different from the faecal microbiota . Interestingly the level of inter‐individual variation of microbiota was present at much lower level in gastric and duodenal samples when compared to stool samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, although it is not frequently addressed, it appears that gastric and duodenal microbiota share many common features . Microbiota analysis of African children showed that the stomach and duodenum microbiota are alike but different from the faecal microbiota . Interestingly the level of inter‐individual variation of microbiota was present at much lower level in gastric and duodenal samples when compared to stool samples.…”
Section: Resultsmentioning
confidence: 99%
“…7 Several studies have also detected representatives of other uncultured bacteria designed as hypothetical phylum SR1. [8][9][10][11] Still, there was a significant overlap with previous cultivation findings, 6,12 mainly because gastric microbes are oxygen tolerant and therefore more readily cultured and described compared to the predominantly anaerobic colonic microbiota.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Given the capacity of Shigella to acquire and accumulate multiple antibiotic resistances (Njamkepo et al, ), this vaccine remains more than ever indispensable. Over the past 15 years, Philippe and his collaborators have progressively extended their expertise to the field of host–microbiota interactions, with notably the goal to understand how the gut can aggravate or, on the contrary protect, against stunting and environmental enteropathy, a devastating condition that increases susceptibility to infections and impairs the development of young children in developing countries (Vonaesch et al, ; Vonaesch et al, ). The interest of Philippe into host–microbiota provided our team with the chance to set up the very rewarding collaboration that is discussed below to study an unusual symbiont, segmented filamentous bacteria (SFB).…”
Section: Introductionmentioning
confidence: 99%